V.2 - Singhvi, L. M. (New Delhi, 2006)
An article-wise second edition of pioneer commentary on the Constitution of India thoroughly revised and enlarged with all the changes made upto the Constitution (93rd Amendment) Act, 2005 and the numerous judgments of Supreme Court and High Courts on vital points have been incorporated with exhaustive coverage on Fundamental Rights, Human Rights, Constitutional Remedies, Fundamental Duties, Service Matters, Reservation for Backward Classes, Ecological Balance, Environmental Protection, Public Interest Litigation, Judicial Review, Judicial Activism & Panchayat Raj etc.
Keywords: Constitution-India